2014
DOI: 10.4148/1944-9771.1063
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Financial Stress among College Students

Abstract: Concerns that debt loads and other financial worries negatively affect student wellness are a top priority for many university administrators. Factors related to financial stress among college students were explored using the Roy Adaptation Model, a conceptual framework used in health care applications. Responses from the 2010 Ohio Student Financial Wellness Survey were analyzed using proportion tests and multivariate logistic regressions. The results show that financial stress is widespread among students -71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
88
2
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(117 citation statements)
references
References 24 publications
9
88
2
6
Order By: Relevance
“…The importance of self-efficacy in this model corresponds to previous studies that demonstrate the salience of self-efficacy in the association between stress and personal well-being in the context of economic stress (Chen & Lim, 2012;Lim, Heckman, Montalto, & Letkiewicz, 2014;Liu et al, 2014). The findings indicate a similar pattern among whites, blacks, and Latinos with respect to self-efficacy and financial strain, the study's outcome measure.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The importance of self-efficacy in this model corresponds to previous studies that demonstrate the salience of self-efficacy in the association between stress and personal well-being in the context of economic stress (Chen & Lim, 2012;Lim, Heckman, Montalto, & Letkiewicz, 2014;Liu et al, 2014). The findings indicate a similar pattern among whites, blacks, and Latinos with respect to self-efficacy and financial strain, the study's outcome measure.…”
Section: Discussionsupporting
confidence: 58%
“…In a meta-analysis of job search interventions, Liu et al (2014) found the odds of obtaining employment increased with interventions that included a component that boosted self-efficacy. Lim et al (2014) found that college students with high financial self-efficacy were more likely to seek help from professionals when they were experiencing financial stress. A recent review of interventions used to negate the harm of debt and job loss on mental health (see Moore et al, 2017 review a discussion of interventions) found mixed results.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a majority of college students (90%) who did not have the financial resources to get involved in the same activities as their friends reported feeling financial stress, thus impacting their overall relationship with friends (e.g., less time spent together; Heckman et al, 2014). According to Britt and Huston (2012), college students who had greater perceptions of personal mastery and higher net worth reported feeling less stressed about their financial situations.…”
Section: Transitionsmentioning
confidence: 99%
“…Prior research has shown that 71% of college students have had a consistent challenge in overcoming financial stress (Heckman, Lim, & Montalto, 2014;Trombitas, 2012). In fact, a majority of college students (90%) who did not have the financial resources to get involved in the same activities as their friends reported feeling financial stress, thus impacting their overall relationship with friends (e.g., less time spent together; Heckman et al, 2014).…”
Section: Transitionsmentioning
confidence: 99%
“…The financial strain caused by suboptimal borrowing to finance college may reduce academic performance or delay college completion (Heckman et al 2014). Over the longer term, graduation with a significant amount of student loan debt has been loosely associated with numerous adverse outcomes, such as delays in forming independent households and reduced homeownership (Brown et al 2015;Dettling and Hsu 2014).…”
mentioning
confidence: 99%